2017
DOI: 10.1158/0008-5472.can-17-1294
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 Is a Biomarker and Regulator of Glioma Stem Cells That Is Critical for Mesenchymal Transition in Glioblastoma

Abstract: Glioma stem cells (GSCs) and epithelial-mesenchymal transition (EMT) are strongly associated with therapy resistance and tumor recurrence, but the underlying mechanisms are incompletely understood. Here we show that S100A4 is a novel biomarker of GSCs. S100A4+ cells in gliomas are enriched with cancer cells that have tumor-initiating and sphere-forming abilities, with the majority located in perivascular niches where GSCs are found. Selective ablation of S100A4-expressing cells was sufficient to block tumor gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 45 publications
5
83
0
Order By: Relevance
“…While knock-down of S100a4 expression and inhibition of S100a4 signaling improves tendon healing, S100a4 can also function in a cell-autonomous manner (31). To determine the effects of S100a4 + cell ablation on tendon healing, we depleted proliferating S100a4 + cells from D5-10 post-surgery (immediately preceding peak S100a4 expression) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While knock-down of S100a4 expression and inhibition of S100a4 signaling improves tendon healing, S100a4 can also function in a cell-autonomous manner (31). To determine the effects of S100a4 + cell ablation on tendon healing, we depleted proliferating S100a4 + cells from D5-10 post-surgery (immediately preceding peak S100a4 expression) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GBM is characterized by complex tissue heterogeneity, in which there is a class of stem cell-like tumor-initiating cells, called GSCs, which have the ability to self-renew, grow continuously and differentiate into multiple neural cell types [34][35][36]. Further studies found that GSCs are key factors leading to the occurrence, recurrence, treatment tolerance and poor prognosis of glioma [35,[37][38][39][40]. We successfully propagated eight human GSC lines with four different molecular subtypes and found the highest PSAP expression and secretion in mesenchymal GSCs, as determined by western blotting and ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…The combined gain of S100A4 and loss of membrane E-cadherin in cervical cancer tends to confirm its link with an unfavorable prognosis [8]. Moreover, the role of this biomarker as a central node in a molecular network controlling stemness and EMT has been reported in one of the most aggressive tumors, glioblastoma [9], providing the initial parts of an answer to the question of the relationship between these two processes [10].…”
Section: Introductionmentioning
confidence: 91%